Factors influencing the customer to adopt e-banking: A study of full-fledged Islamic bank in northern region of Malaysia - Nur Ainil Khairina, Ibrahim (2018)
Electronic banking or known as e-banking is not a new phenomenon to the people nowadays. Developments in information technology and telecommunications have set in motion an electronic revolution in the Malaysian banking sector. Starting with the Automated Teller Machines (ATM) in 1970s till the introduction of Internet banking in the year 2000s, electronic banking has become an important product and services provided by the banking institutions including Islamic banks in Malaysia. This study aims to explore the factor influencing the customer to adopt e-banking in Islamic bank. The determinants obtained by the researcher from the previous studies are perceived ease of use, security, speed, and fees and charge. Questionnaires are distributed to 400 customers of Islamic banks. Out of total 400 respondents, 376 questionnaires were usable. The finding shows all the independent variables are positive correlated with customer to adopt e-banking. Analysis shows all the determinants have a positive relationship with the customers to adopt e-banking in Islamic banks. This result reported in this research are useful the bankers to improve their system and giving consumers an awareness of the advantages of using product and services in Islamic bank. In future research, other variables can be explored to study on the researcher recommended to specific categories of customer bank which is from the generation Z because they born and grow up in digital era with a variety of sophisticated technologies. In addition, from that study can identify the awareness about religiosity and the halal product and services among the young generation.